PELATIHAN PEMBUATAN DESAIN KAOS SABLON DAN SOUVENIR BERBAHAN KERAMIK PADA KARANG TARUNA KAMPUNG WISATA KERAMIK DINOYO MALANG UNTUK MENUMBUHKAN SEMANGAT BERWIRAUSAHA - Ita Rifiani Permatasari; Anik Kurmintarti; Suselo Utoyo; Tri Yulistyawati Evelina (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2019)
The training to make screen printing t-shirt designs and souvenirs made from ceramics at Karang Taruna Village, Dinoyo Malang Tourism Village aims to: (1) Karang Taruna, Dinoyo Ceramic Tourism Village in Malang able to make a t-shirt design, as well as screen printing for the t-shirt (2) Youth club (Karang Taruna) of Dinoyo Tourism Village Malang also able to make souvenir designs made of ceramics (3) Karang Taruna Malang Dinoyo Ceramic Village is able to apply the design of T-shirts and souvenirs made from ceramics into screen-printed T-shirt products and souvenirs made from ceramics that are worthy to be marketed or sold as souvenirs for tourists visiting the Dinoyo Ceramic Tourism Village in Malang (4) Karang Taruna Malang Dinoyo Ceramic Tourism Village has the skills to produce screen printing t-shirts and souvenirs made from ceramics so that it can foster enthusiasm to start a new business (entrepreneurship). The training method used is to use lecture, question and answer, discussion, apprenticeship and direct practice methods for making designs for screen printing t-shirts and merchandise. The results obtained from this training are (1) Training participants (Karang Taruna Dinoyo Ceramic Tourism Village) are able to understand the concept of making designs that reflect the uniqueness of Malang Dinoyo Ceramic Tourism Village, (2) Training participants are skilled in making or applying designs into screen printing t-shirts and souvenirs made of ceramics typical of Malang Dinoyo Ceramic Tourism Village. (3) Participants are able to develop the results of their training into a product that is worth selling so as to produce economic value for themKey words: service quality, online shop